ANALISIS TINGKAT KEPUASAN TAMU GRUP TERHADAP FASILITATOR TEAM BUILDING DI CORE NATIVES - Lukmanul Hakim; Achlan Fahlevi Royanow; Ida Ayu Yadnya Sari Dewi Utami Pidada (Bajang Institute, 2024)
Core Natives is one of the team-building facilitators in Lombok. To determine customer satisfaction, Core Natives uses conventional methods and is not yet representative. So it is necessary to carry out scientific studies regarding customer satisfaction. This research aims to determine the level of satisfaction of group guests towards team building facilitators at Core Natives. There are five dimensions of service quality from the SERVQUAL (Service Quality) theory, namely Reliability, Responsiveness, Assurance, Empathy, and Physical Evidence. The Customer Satisfaction Index (CSI) method is used to determine the level of customer satisfaction which refers to service dimensions. The quantitative method is a descriptive approach using questionnaires to collect data. From a total of 180 participants, a sample of 119 people was determined for an error rate of 5%. In this research, a Likert scale of 1-5 was used. Then the data was processed using IBM SPSS statistics with version 29 to test the validity and reliability of the data, and Microsoft Excel to calculate the mean and CSI values. With a CSI value of 94.15%, the level of group guest satisfaction with the team-building facilitator at Core Natives is in the very satisfied category. It was concluded that statement P10 which is an attribute of Physical Evidence (Tangibel) received the highest mean value of 4.7983 with the contents of the facilitator's statement using team building tools that were well maintained